Prevalence of metabolic syndrome and associated factors in adults living in Fernando de Noronha, Brazil - Mulatinho, Letícia M. [UNESP]; Ferraz, Ana Paula C.R. [UNESP]; Francisqueti, Fabiane V. [UNESP]; Garcia, Jéssica L. [UNESP]; de Souza, Claudinalle F.Q.; Cardoso, Mirian D.; Lemes, Kelly C.T.; Mesquita, Milca V.C.O.; Corrente, José Eduardo [UNESP]; dos Santos, Klinsmann C. [UNESP]; Corrêa, Camila Renata [UNESP] (Elsevier, 2019)
Metabolic Syndrome (MetS) is multivariate disease, clustered with socioeconomic and behavioral risk factors. Investigations about epidemiology estimative could be a prevention strategy. Aim: to investigate the prevalence of metabolic syndrome and its associated factors in adult population in Fernando de Noronha Archipelago (PE-Brazil). Methods: A cross-sectional study was performed on a representative sample (N = 375) of adult residents of the region, aged 24–59 years, were harmonized according to the International Diabetes Federation (IDF) criteria. Results: The prevalence of metabolic syndrome was 45 (12%) and, the age was associated with MetS, which increases the chances to MetS development around 3% respectively (OR: 1.03; CI 95%: 1.002–1.070 P 0.0384). Waist circumference was elevated in female population 266 (70.74%), however, levels of fasting blood glucose (304 [80.85%]), blood pressure (375 [100%]), TG (302 [80.32]), and low HDLc (297 [78.99]) presented normal biochemical values. There is no significative difference for male and female gender and, the social and behavior factors did not present significative association. Conclusion: The Fernando de Noronha presents lower prevalence of MetS thus, shows associations for elderly people. The waist circumference was elevated on female population. The results of this study provide further evidence and underscore the need for public health strategies that include education about MetS, promotion of cardiometabolic health, and prevention of undesirable outcomes such as diabetes and cardiovascular disease.
Keywords: Metabolic syndrome; Obesity; Public health